Report on Ex-Post Evaluation of Rajrappa Opencast Coal Project of Central Coalfields Limited (A Case Study) - Planning Commission (Planning Commission Government of India, 1995)
The Ex-Post Evaluation of the Rajrappa Opencast Coal Project examines the operational, financial, and social challenges of a large-scale coal mining initiative under Central Coalfields Limited. Originally sanctioned in 1963 with an annual capacity of 1.5 MTPA, the project was revised to 3.0 MTPA and completed in 1990 with 86% capacity utilization. The evaluation identifies significant delays and cost overruns, with capital costs escalating by 46% and project timelines extended by five years due to pit-head washery commissioning delays, village relocation, and infrastructure setbacks. Operational challenges included low utilization of heavy earth moving machinery, inadequate preliminary geological studies, and suboptimal productivity. Environmental and social issues, such as delayed rehabilitation and land acquisition, affected community relations and project efficiency. The report recommends improved project planning, integrated coal-washery development, enhanced geotechnical assessments, timely land acquisition and rehabilitation, and systematic equipment maintenance to optimize performance. Complementary analyses of capital allocation for infrastructure, water supply, and land reclamation projects highlight the importance of budget monitoring, financial accountability, and maintenance oversight. The findings emphasize that incorporating lessons from this evaluation is essential for improving efficiency, reducing costs, and ensuring sustainable outcomes in future large-scale mining and infrastructure projects.
Government of India Planning Commission Project Appraisal & Management Division New Delhi January 1995
Government of India Planning Commission Project Appraisal & Management Division New Delhi January 1995
Keywords: Rajrappa Opencast Coal Project; Central Coalfields Limited; Cost Overrun; Time Overrun; Heavy Earth Moving Machinery; Coal Production; Land Acquisition; Environmental Management; Rehabilitation; Capital Allocation; Infrastructure Projects; Operational Efficiency